Proceedings of the second international symposium on the management of large rivers for fisheries. - Welcomme, R. and T. Petr (eds). (Bangkok, Thailand FAO Regional Office for Asia and the Pacific, 2004)
2 vol.
Keywords: Biodiversity--Congresses.; Sustainable livelihoods; River fisheries--Congresses.; Fishery management--Congresses.